Pemanfaatan Grup Whatsapp sebagai Media Informasi Proses Belajar Anak di KB Permata Bunda - Nur Lailatul Fitri (Universitas Al-Hikmah Indonesia, 2019)
This study aims to describe: 1) how is the delivery of information on the learning process of children at KB Permata Bunda? 2) how to use whatsapp group? 3) what are the positive and negative impacts of using whatsapp groups as information media? The data collection method `is in the form of observation, interview and documentation. The results showed: 1) the delivery of information on academic development at KB Permata Bunda Gesikharjo was through a contact book that was distributed once every 3 months, while those related to the KBM process through letters, meetings and messages. 2) whatsapp group is used as a daily link between teacher and student guardians. 3) some positive effects felt by parents of KB Bunda Gesikharjo KB students including they can find out information on children's development at school quickly even though they have other activities outside of school, while the negative impact is more related to time and grammar in written communication..